Genomic Epidemiology and Evolution of Scallion Mosaic Potyvirus From Asymptomatic Wild Japanese Garlic - Ohshima, Kazusato; Kawakubo, Shusuke; Muraoka, Satoshi; Gao, Fangluan; Ishimaru, Kanji; Kayashima, Tomoko; Fukuda, Shinji (Frontiers in Microbiology, 2021)
Scallion mosaic virus (ScaMV) belongs to the turnip mosaic virus (TuMV) phylogenetic group of potyvirus, and is known to infect domestic scallion plants (Allium chinense) in China and wild Japanese garlic (Allium macrostemon Bunge) in Japan. Wild Japanese garlic plants showing asymptomatic leaves were collected from different sites in Japan during 2012–2015. We found that 73 wild Japanese garlic plants out of 277 collected plants were infected with ScaMV, identified by partial genomic nucleotide sequences of the amplified RT-PCR products using potyvirus-specific primer pairs. Sixty-three ScaMV isolates were then chosen and those full genomic sequences were determined. We carried out evolutionary analyses of the complete polyprotein-coding sequences and four non-recombinogenic regions of partial genomic sequences. We found that 80% of ScaMV samples have recombination-like genome structure, and identified 12 recombination type patterns in the genomes of the Japanese ScaMV isolates. Furthermore, we found two non-recombinant type patterns in the Japanese population. Because the wild plants and weeds may often serve as reservoirs of viruses, it is important to study providing the exploratory investigation before emergence in the domestic plants. This is possibly the first epidemiological and evolutionary study of a virus from asymptomatic wild plants.